Analisis Kualitas Pelayanan terhadap Kepuasan Masyarakat pada Kantor Kecamatan Inamosol - KWALOMINE, FRETS; NATANIEL, ELAKE (Patria Artha Management Journal, 2022)
This study aims to determine the quality of service at the Inamosol District Office and the level of community satisfaction, as well as to examine the relationship between service quality conditions at the Inamosol District Office and the level of community satisfaction. The data analysis technique used in this study is quantitative associative using a questionnaire that has been tested to be valid and reliable. To test the direction of the relationship between the independent variable and the dependent variable, the Product Moment correlation was used. Based on the results of the analysis, it is known that the quality of service at the Inamosol District Office, West Seram Regency is classified as moderate or quite good. The level of community satisfaction with service quality at the Inamosol District Office is moderate or the community is quite satisfied with the services at the Inamosol District Office, West Seram Regency. It is proven that there is a relationship between service quality conditions at the Inamosol District Office and the level of community satisfaction. This is indicated by the correlation coefficient (R) of 0.501, which means that there is a fairly strong positive relationship. It means that to increase community satisfaction, the service quality of the Inamosol District Office also needs to be improved.